Sistem Informasi Pengarsipan Dokumen Berbasis Website dengan Metode Agile Software Development - Laksana, Bagastian Tri; Yulia, Eka Rini (Universitas Respati Indonesia, 2024)
the need for information technology and computerization is getting higher and growing very quickly. The application of technology in today's business is unavoidable. One way that companies can compete with their competitors is to use a good information system, which aims to simplify and improve the quality of professional work. Archives are sources of information that have an important role in supporting the administrative and management activities in the company. We need a web-based application that can store archives and can simplify the document archiving process. The design of the information system uses the Extreme Programming model. By using Extreme Programming, information systems can record and accommodate every archiving need properly. This research is expected to help the employees of PT. Propack Kreasi Mandiri to store and searching for document information.